Seawater oxygenation during the Paleocene-Eocene Thermal Maximum - Dickson, A; Cohen, A; Coe, A (2012)
Uncertainty over the trajectory of seawater oxygenation in the coming decades is of particular concern in the light of geological episodes of abrupt global warming that were frequently accompanied by lowered seawater oxygen concentrations. Here we present an assessment of global seawater oxygenation from an interval of one of these warming episodes, the Paleocene-Eocene Thermal Maximum (PETM, 55.9 m.y. ago). Our results, obtained from Integrated Ocean Drilling Program Expedition 302 Site M0004 in the Arctic Ocean, are based on molybdenum isotope determinations and molybdenum, rhenium, and uranium abundances. These data indicate a small global expansion of low-oxygen marine environments in the upper part of the PETM interval compared with the present day. More extensive seawater deoxygenation may have occurred for as long as ~100 k.y., associated with a high rate of global warming and carbon oxidation at the start of the PETM. Our data also reveal molybdenum isotope compositions in Arctic Ocean deposits that are outside the range currently documented in marine environments. These exceptional compositions could reflect either the influence of hydrothermal inputs or equilibrium isotope fractionations associated with molybdenum sulfide speciation. © 2012 Geological Society of America.